Photodynamic therapy for polypoidal choroidal vasculopathy secondary to choroidal nevus - Wong, James G (Int Med Case Rep J, 2017)
We report a case of a Caucasian female who developed active polypoidal choroidal vasculopathy (PCV) at the edge of a stable choroidal nevus and was successfully treated with verteporfin photodynamic therapy. No active polyp was detectable on indocyanine green angiography 2 years after treatment, and good vision was maintained. Indocyanine green angiography is a useful investigation to diagnose PCV and may be underutilized. Unlike treatment of choroidal neovascularization secondary to choroidal nevus, management of PCV secondary to nevus may not require intravitreal anti-vascular endothelial growth factor therapy. Photodynamic monotherapy may be an effective treatment of secondary PCV.